Tanggung Jawab Negara Terhadap Kegiatan Agen Diplomatik Di Luar Misi Diplomatik Berdasarkan Hukum Internasional - Oktrina, Faiha; Waryenti, Deli; Muthia, Arini Azka (UNIB Press, 2023)
States send their representatives to other states for diplomacy, these state’s representatives are referred to in Diplomatic Law as 'diplomatic agents'. According to Article 3 of the 1961 Vienna Convention, a diplomatic agent has a diplomatic mission in the form of: representing the government of the sending state; protecting their citizens where they accredited; promoting their country; negotiating; and reporting all tasks that have been done to the government of their state. However, in practice, it is not uncommon for diplomatic agents to carry out activities outside of diplomatic missions. This study analyzes the state's responsibility to diplomatic agents who carry out missions outside of diplomatic missions based on International Law and the legal implications for diplomatic agents who carry out missions outside of diplomatic missions. The research method used normative legal research with statutory, case, and doctrinal approaches. Responsibility can be done as long as there are objections from the state that impact some disadvantaged. Consider the diplomatic law based on an agreement between the two states that establish diplomatic relations.